Novel Cu2O gas sensor prepared by potentiostatic electrodeposition on IDE electrodes. (September 2019) - Mikolasek, M; Meri, J; Chymo, F; Ondrejka, P; Rehacek, V; Predanocy, M; Kostic, I; Hotovy, I
Abstract: This paper introduces a new approach for preparation a gas sensor based on the potentiostatic electrodeposition of Cu2 O on interdigitated electrodes. Four Cu2 O gas sensors with different deposition charges were prepared from lactate-stabilized copper sulphate on Au IDE electrodes. Prepared sensors were characterised by scanning electron microscopy and electrical measurements in the air and H2 ambient. It was found that the key aspect for high gas sensitivity is to achieve an appropriate rate of crystal interconnection between IDE electrodes. Low deposition charge results in an air gap between IDE electrodes, while high deposition charge causes strong, bulk-like interconnection of Cu2 O crystals. The low rate of Cu2 O interconnection formed by connection of individual crystals, where the conductance is affected by the surface area of the crystals, is shown as a most appropriate sensor. The sensitivity of 3.75 to 1000 ppm H2 concentration and 200 °C operation temperature is achieved for the optimised Cu2 O based IDE sensor.